A high-energy passively Q-switched Yb-doped fiber laser based on WS2 and Bi2Te3 saturable absorbers. (23rd August 2017) - Wang, Junli; Li, Sha; Xing, Yupeng; Chen, Lei; Wei, Zhiyi; Wang, Yonggang
Abstract: In this paper, we report two different saturable absorbers based on WS2 film and Bi2 Te3 film with similar preparation processes. A high-energy stable Q -switching pulse is achieved in identical cavity configurations for each absorber. A modulation depth of 10.17% and a maximum single pulse energy of 56.50 nJ are obtained when employing the WS2 film. However, using the Bi2 Te3 film we obtain a higher modulation depth of 23.04% and a larger single pulse energy of 61.80 nJ, and stable dual-wavelength Q -switching operation was shown at a pump power of 92 mW.